(untitled) (Ibrahim Cardiac Medical Journal, 2026)
Background & objective: Cervical cancer is a leading cause of cancer-related mortality in women in Bangladesh and other developing countries. Early diagnosis and treatment of premalignant lesions are essential for prevention. This study aimed to evaluate and compare the diagnostic accuracy of three cervical cancer screening methods-Visual Inspection with Acetic Acid (VIA), Conventional Cytology (Pap smear), and Human Papillomavirus (HPV) DNA testing-to inform screening policies in a local setting. Methods: This cross-sectional descriptive study was conducted from January to December 2022 at the Gynecological Oncology Department of National Institute of Cancer Research and Hospital (NICRH), Dhaka. A total of 100 women aged 25-65 with symptoms and signs suggestive of cervical pathology or suspicious cervical findings on naked eye examination were enrolled. All participants underwent screening with VIA, Pap smear, and HPV-DNA tests, with histopathology serving as the gold standard. Diagnostic accuracy measures, including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy, were calculated. Cohen’s Kappa statistic was used to assess the inter-rater reliability among the three tests. Results: HPV-DNA testing demonstrated the highest overall diagnostic accuracy at 89%, with a sensitivity of 68.2% and a specificity of 94.9%. Pap’s smear (conventional cytology) showed high specificity (98.7%) but poor sensitivity (31.8%), resulting in an overall accuracy of 84%. VIA had a moderate sensitivity (54.5%) but a low specificity (74.4%), with an overall accuracy of 70%. The inter-rater agreement between the three tests was found to be poor to fair, with Cohen’s Kappa values of 0.290 (HPV-DNA vs. Pap), 0.202 (HPV-DNA vs. VIA), and 0.197 (VIA vs. Pap). Conclusion: The findings suggest that HPV-DNA testing is the most accurate diagnostic tool for detecting premalignant cervical lesions. Its superior performance in sensitivity, specificity, and overall accuracy makes it the most effective screening modality. These results support a strategic shift towards an HPV-DNA-based national screening program in Bangladesh to improve early detection and reduce the burden of cervical cancer. Ibrahim Card Med J 2024; 14 (2): 37-44